Vietnam's Labor Market Institutions, Regulations, and Interventions : Helping People Grasp Work Opportunities in a Risky World - Schmillen, Achim D.; Packard, Truman G. (World Bank, Washington, DC, 2016)
Over the past 30 years, Vietnam has experienced significant shifts of employment away from agriculture toward manufacturing and services, away from household enterprises toward registered and regulated businesses, and away from state-owned enterprises toward private firms. This paper argues that for these processes to continue in the future, appropriately designed and implemented labor market policies need to be in place, including labor market regulations that protect workers but do not inhibit creative destruction and creation of formal sector jobs; labor market interventions that improve workers' human capital, eliminate information asymmetries, and are fiscally sustainable; and labor market institutions that give voice to workers and employers. As a part of all of these measures, Vietnam will also have to renew its efforts to integrate vulnerable groups into the labor market.